Efektifitas Iklan Pada Keputusan Nasabah BPRS Di Madura - Rudy Haryanto (Institut Agama Islam Negeri Madura, 2019)
The tight competition between Islamic financial institutions, BPRS in Madura seeks to maintain its existence. Acceleration of the program to increase capacity to be more competitive in developing its business is absolutely necessary in order to maintain business continuity, one of which is through the optimization of the marketing sector. Advertisements are promotional facilities used by BPRS to inform everything about their products. To optimize the function of advertising, the information provided must include product benefits, product prices and product benefits compared to competitors. For this reason, the analysis of this research uses the AIDA concept, namely Attention, Interest, Desire and Action. This study aims to determine the effectiveness of advertising by using the AIDA concept on the decision to become a customer of a BPRS in Madura. The results of the study show that AIDA simultaneously has a significant effect on the decisions of the customers of BPRS in Madura. This is evidenced by the coefficient of determination of AIDA's ability to explain its influence on the decision to become a customer of a BPRS in Madura by 82.4% and 17.6% explained by other variables not examined. While partially AIDA significantly influences the decision to become a customer of a BPRS in Madura with a significance level of 2.4%, 1.4%, 0.08% and 0.02%, respectively. Based on these facts, the most dominant AIDA concept influencing the decision to become a customer of a BPRS in Madura is the Action substance with a significant value of 0.02%.[Ketatnya persaingan antar lembaga keuangan syariah, BPRS Di Madura berusaha mempertahankan eksistensinya. Akselerasi program peningkatan kemampuan untuk lebih kompetitif dalam mengembangkan bisnisnya mutlak diperlukan agar bisa mempertahankan keberlangsungan usaha, salah satunya melalui optimalisasi sektor marketing. Iklan adalah sarana sarana promosi yang digunakan oleh BPRS guna menginformasikan segala sesuatu produknya. Guna mengoptimalkan fungsi iklan, informasi yang diberikan harus mencakup manfaat produk, harga produk serta keuntungan-keuntungan produk dibandingkan dengan pesaing. Untuk itu analisis iklan dalam penelitian ini menggunakan konsep AIDA yaitu Attention, Interest, Desire dan Action. Penelitian ini bertujuan untuk mengetahui efektifitas iklan dengan menggunakan konsep AIDA pada keputusan menjadi nasabah BPRS di Madura. Hasil penelitian menunjukan bahwa secara simultan AIDA berpengaruh secara siknifikan terhadap keputusan nasabah BPRS di Madura. Hal ini di buktikan berdasarkan koefisien determinasi kemampuan AIDA menjelaskan pengaruhnya terhadap keputusan menjadi nasabah BPRS di Madura sebesar 82,4% dan 17,6 % dijelaskan oleh variabel lain yang tidak diteliti. Sedangkan secara parsial AIDA berpengaruh secara siknifikan juga terhadap keputusan menjadi nasabah BPRS di Madura dengan tingkat siknifikansi masing-masing 2,4 %, 1,4%, 0,08% dan 0,02%. Berdasarkan fakta tersebut konsep AIDA yang paling dominan mempengaruhi keputusan menjadi nasabah BPRS di Madura adalah subtansi Action dengan nilai siknifikan 0,02%.]